Mathematical modelling and analysis of solar water collector with flat and V-groove absorber plate with helical and plain water flow path tubes. Issue 4 (August 2020) - Navakrishnan, S; Sudhakar, P
Abstract: A mathematical model for Solar Flat Plate Collector (SFPC) has been developed to compare the thermal performance between different geometrical profiles of the collector like Flat plate, V-groove absorber plate and with plain and helical strip inserted in the absorber tube. Water, used as working fluid, is passed through the tubes to investigate the thermal performance. Different geometry of the absorber plate and tube are used to increase the heat gain by the collector. The temperatures at inlet and outlet are measured and analysis of collector recovery factor, heat gain, losses like bottom loss, edge loss and efficiency of collector has been done. The comparative study on the thermal performance shows 4% higher collector efficiency for helical strip absorber tube than the other geometric profiles. Also, the results of mathematical analysis closely agree with the experimental results.